Revenance - Hogue, Cynthia (Book collections on Project MUSE., 2014)
"By turns elegiac, ecopoetic, and impolitic, Cynthia Hogue's eighth collection, Revenance, is a condensery of empathic encounters with others and otherness. Hogue coins a word--from revenant, French for 'ghost'--to consider questions of life and afterlife, and to characterize the ways in which the people and places we love return to us, and return us to ourselves, holding us to account. The poems of Revenance contain telling touchstone figures, like a guide named Blake who, noting signs of global warming, will speak of spirits but not angels; a man who dies and is brought back to life by the imaginative power of love; and a woman who can speak the language of endangered trees. While writing these poems, Hogue journeyed often across country to her familial roots in upstate New York in order to help care for her dying father. At last she began to record some of the many stories she heard of mysterious encounters and visitations, such as she herself was soon to witness, over several intensive years. Although grief silvers the threads of these poems, Hogue pares away the personal in order to be present to others in a fiercely engaged and innovative poetry"--